(untitled) (JOURNAL OF INNOVATIVE RESEARCH IN MANAGEMENT AND HUMANITIES, 2012)
This research sought stakeholders’ views toward the combined use of traditional and modern medicine on hospitalized patients. The research contributes towards indigenous knowledge systems in Zimbabwe. The research is a survey carried out at Chinhoyi Provincial Hospital. Questionnaires and an interview guide were used. The respondents were doctors, nurses, patients and relatives of the hospitalised patients. Data was presented in frequency distribution tables. The findings revealed that traditional medicine was being used on hospitalized patients. Health professionals, patients and their relatives strongly believe that traditional medicine cures. The research findings led to the following recommendations; patients and relatives should be educated on the complications associated with combined use of traditional and modern medicine on hospitalized patients, and policy makers need to facilitate dialogue between the Ministry of Health and Child Welfare, health professionals and traditional healers to map the way forward on integration of modern and traditional medicine. There is need of a further study to establish traditional healers’ views on the integration of traditional and modern medicine to compliment findings of this study.